2005
DOI: 10.1001/archotol.131.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Multiplanar Computed Tomographic Analysis of Frontal Recess Cells

Abstract: Background: Frontal recess anatomy can be very complex, with accessory cells such as frontal, agger nasi, and intersinus septal cells encroaching on the frontal recess and possibly contributing to obstruction of the frontal sinus. In this study, we determined the prevalence of these cells and their relationship to frontal sinusitis in patients who have (revision group) and have not (primary group) had previous sinus surgery.Design: Multiplanar computed tomographic images were reconstructed on a computer workst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 13 publications
(21 reference statements)
9
84
3
Order By: Relevance
“…Del Gaudio JM et al, (2005) studied 106 CT PNS and found type I frontal cells most common in 18.1% followed by type III in 6.1%, type IV in 2.4% and type II in 1.4% cases [31]. Finding of our study correlated well with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…Del Gaudio JM et al, (2005) studied 106 CT PNS and found type I frontal cells most common in 18.1% followed by type III in 6.1%, type IV in 2.4% and type II in 1.4% cases [31]. Finding of our study correlated well with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…Over all in our study out of 50 cases, 37 patients had frontal recess cells (74 %). According to Delgaudio et al [18] overall incidence of frontal recess cells in their study was 33 %. Likewise Meyer et al [3] found that incidence of frontal recess in their study was 20.4 %.…”
Section: Discussionmentioning
confidence: 78%
“…Delgaudio et al [18] has found that type 1 frontal recess cells were most common, found in 15.6 % of cases overall and type 2 cells were found in 1.4 % of cases, type 3 in 6.2 % of cases and type 4 in 2.4 % of cases. In our study prevalence of type 1 frontal recess cell was 44 %, type 2-8 %, type 3-48 % and type 4-2 % of cases, as compared to Lee et al [15] (37, 19, 8, and 0 %).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, frontal sinus disease correlates with the severity of overall sinus disease as determined by sinus CT scan [20]. Delgaudio et al [21] reported there was no relationship between AN cells and the incidence of frontal sinusitis. In the study of Fadda et al [3] AN cells were detected in 24.3 % of cases, and was associated with frontal sinusitis in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%